Kewenangan Notaris Membuat Akta Yang Berkaitan Dengan Pertanahan Menurut Pasal 15 Ayat (2) Huruf (F) Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris - Dela Cahyani (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Abstract : That the formulation of clause 15 verse (12) point (0 statute number 30 in 2004 about notarist occupation which states that notarist has an authority to issue the official documents related to the land affairs, practically it can cause the difference in interpratation. At glance, the statement itself can create the assumption that notarist occupies the authority of PPAT in issuing land official document (akta PPAT).Having done the analysis of juridical-normative, furthermore, it is done by the statute approach as well as the law history and sistematical interpretation, with legal materials of primary and secondary so that this study obtains that:The authority of notarist as stated in the clause 15 verse (2) point (f) statute number 30 in 2004 must be interpreted narrowly, it means that notarist does not occupy the authority of PPAT in issuing the land official documents and there is no conflict of authority between the authority of notarist and PPAT that they are different each other either seeing from historical aspect, law background, or the scope of its job. The formulation is formulated by the statute makers in order to anticipate a very quick development in economy and business so that it is expected to be able to accept any kinds of economic and business activities in community that do law action or the agreement related to land affairs;The interpretation of notarist authority that issues the official documents related to land affairs that belongs to the authority of PPAT until now. The authority of notarist in issuing land official documents is the authority that is described as follows: the notarist official document is the official document that contains with law affairs stated in the agreement which is obligatory, that its object related to land affairs, nevertheless, the concerned law affairs is not aimed to shift the right of land ownership or to burden the right of land ownership, for instance the official document of rent-lease agreement or the land official document of borrow-use agreement;According to the findings above, this study concludes that the authority of notarist in issuing official document related to land affairs is not the authority of issuing land official document that belongs to PPAT business, and the authority of notarist is done as long as the official document that they make has no tendency to shift the right of land ownership or to burden the right of land ownership. At last, this study suggests that : (a) in order to make the interpretation to the clause 15 verse (2) point (f) statute number 30 in 2004 is implemented by law history interpretation and systemic interpretation, (b) in order to make the authority of PRAT increases its law basis to be statute, and (c) it is expected to all intergrated relationship to conduct thesocialization and coordination in order that the conflict of authority does not occur between notarist and PPAT when they work. (keywords: The Authority, Official Document, Land)